Changes in step characteristics during sprint performance development - Charalambous, L.; Kerwin, D. G.; Irwin, G.; Bezodis, I. N.; Hailes, S. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Horizontal sprint velocity is the product of step length (SL) and step frequency (SF), but the relative importance of these step characteristics (SC) to step velocity (SV) remains uncertain. This study monitored changes in SC for three developing athletes over a 5 week training period. SV, SL and SF were calculated from manually digitized, reconstructed (2D-DLT) 50 Hz video co-ordinates of foot contacts in 60 m sprints. Performance (60 m time) and SV improved where each athlete increased the SC that had correlated significantly (p < 0.05) with SV at the start of training. This suggested that developing athletes initially favoured the SC upon which they relied at the start of training. These findings inform sprint coaching and direct further research into biomechanical variables determining SC and their inter-relationships.